Green human resource management and shipping firms’ environmental performance: the serial mediating effects of seafarers’ organizational commitment and green behavior - Jiaqi Liu; Hongbo Wang; Xin Wen; Hongyu Zhang; Yui-yip Lau; Qiong Chen; Xiaoming Zhou (Frontiers in Marine Science, 2026)
This study empirically examines the relationships among green human resource management, seafarers’ organizational commitment, seafarers’ green behavior, and shipping firms’ environmental performance. It further explores the mediating roles of seafarers’ organizational commitment and green behavior. Questionnaire survey data were collected from 519 Chinese seafarers, and structural equation modeling (SEM) was used to test the proposed hypotheses and mediating effects. The results indicate that green human resource management significantly enhances seafarers’ organizational commitment and green behavior, thereby improving shipping firms’ environmental performance. In addition, green human resource management indirectly promotes environmental performance through the single mediating effect of seafarers’ green behavior and the sequential mediating effects of organizational commitment and green behavior. These findings highlight the importance of developing and implementing green human resource management policies for senior managers and human resource departments in shipping companies.